2006
DOI: 10.1038/sj.onc.1209680
|View full text |Cite
|
Sign up to set email alerts
|

Rb family proteins as modulators of gene expression and new aspects regarding the interaction with chromatin remodeling enzymes

Abstract: The pRb family proteins (pRb1/105, p107, pRb2/p130), collectively referred to as pocket proteins, are believed to function primarily as regulators of the mammalian cell cycle progression, and suppressors of cellular growth and proliferation. In addition, different studies suggest that these pocket proteins are also involved in development and differentiation of various tissues. Several lines of evidence indicate that generally pRb-family proteins function through their effect on the transcription of E2F-regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
107
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(112 citation statements)
references
References 81 publications
5
107
0
Order By: Relevance
“…The down regulation of CDK2 and pRb might be responsible for chromatin remodeling [35] that might contribute to sustained down regulation of survivin, the overexpression of which could enhance malignant potential of glioblastomas [36,37]. One of the interesting observations made in the present study was the down regulation of survivin in glioblastoma cells after treatment with 4-HPR alone and also in combination with IFN-γ (Fig.…”
Section: Discussionsupporting
confidence: 59%
“…The down regulation of CDK2 and pRb might be responsible for chromatin remodeling [35] that might contribute to sustained down regulation of survivin, the overexpression of which could enhance malignant potential of glioblastomas [36,37]. One of the interesting observations made in the present study was the down regulation of survivin in glioblastoma cells after treatment with 4-HPR alone and also in combination with IFN-γ (Fig.…”
Section: Discussionsupporting
confidence: 59%
“…Consistent with this finding, The functional consequence of FoxO-mediated disruption of cyclin-CDK complex formation is to decrease the phosphorylation of the pRB family proteins, and hence E2F transcriptional activity. However, FoxO may also directly target the pRB family members p107 and p130 (also called pRB2) (Bandara et al, 1994;Giacinti and Giordano, 2006;Macaluso et al, 2006); mammalian FoxO3a and FoxO4 have been shown to directly activate the transcription of the p130 gene, which can induce cells to undergo cell cycle arrest and enter a quiescent state (Kops et al, 2002b). Interestingly, some cell cycle regulators, including p107, pRB, E2F1-3, cyclin D1, cyclin E1/2, cyclin A1/2, CDK2 and CDC2 are themselves transcriptional targets of E2F-and pRBrelated proteins (Dalton, 1992;Furukawa et al, 1994;Shan et al, 1994;Ohtani et al, 1995;Schulze et al, 1995;Sears et al, 1997;Araki et al, 2003;Cobrinik, 2005).…”
Section: Foxo and The G1/s Phase Transitionmentioning
confidence: 99%
“…This family includes the product of the Rb susceptibility gene, the pRb/p105 protein and the related p107 and pRb2/130 proteins (Mayol et al, 1993;Du and Pogoriler, 2006;Merola et al, 2006). They share the ability to recruit chromatin-remodeling enzymes and their best characterized targets are the members of the E2F/DP family of transcription factors, generally referred to as E2F (Cinti et al, 2005;Tosi et al, 2005;Genovese et al, 2006;Macaluso et al, 2006;Purev et al, 2006). Both pRb2/p130 and p107 are able to bind cdk2/ cyclins A and E (Claudio et al, 1996).…”
Section: Introductionmentioning
confidence: 99%